(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
In the global economy, attracting investments and accelerating economic growth is one of the most important strategic tasks for countries. Especially in the context of increasing globalization and competition, countries strive to implement effective economic mechanisms to attract foreign capital, advanced technologies, and modern management experience. One such mechanism, widely applied in international practice, is the establishment of special economic zones (SEZs), which have proven highly effective.